PENANAMAN NILAI-NILAI IBADAH MELALUI KEGIATAN EKSTRAKURIKULER DI TAMAN KANAK-KANAK AISYIYAH SAWOO PONOROGO - Ikka Widya Kusuma Ningrum; Rido Kurnianto; Rohmadi Rohmadi (Universitas Muhammadiyah Ponorogo, 2021)
The values of worship that are learned and instilled in children from an early age will have an impact on the quality of the next generation who will continue the Islamic da'wah that is stronger, has noble character, and has broad insight. Aisyiyah Sawoo Kindergarten has instilled worship values in accordance with Islamic law which are packaged in the form of extracurricular activities. This study aims to determine the implementation of inculcating religious values through extracurricular activities in TK Aisyiyah Sawoo Ponorogo and knowing the results of the implementation of inculcating religious values through extracurricular activities at TK Aisyiyah Sawoo Ponorogo. This study uses a research method with a qualitative descriptive analysis approach. The results of this study were the implementation of the cultivation of religious values through extracurricular activities at Aisyiyah Sawoo Kindergarten which included creativity, motivation, children's memory, and environmental recognition.